THE NATURE OF OPERATIONAL RESEARCH - Omar, F. (Dirasat in Economics and Business, 1968)
This paper discusses the nature of operational research and the sont of modelling. The paper then looks at a simplified information won dow of a typical company as a basis for indicating some of the main tortical decision areas in the control of production systems: These will include the problems of demand forcasting and inventory control and production planning and control. In each of these areas digital com puters have made the use of new methods possible. Selected problem areas such as shop scheduling where computer simulation has given encouragement to research are then discussed and the paper concludes with the description of a simplified model of the industrial dynamics type.